2020
DOI: 10.7762/cnr.2020.9.3.163
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dietary Vitamin A and C Intakes and Cataract: Data from Korea National Health and Nutrition Examination Survey 2012

Abstract: Oxidative stress in eye lens is one of the main causes of the cataract. Dietary antioxidants including vitamin A and C are therefore known to be associated with the risk of the disease. However, evidences are still lacking in Koreans. This study aimed to examine whether dietary vitamin A and C levels are associated with the cataract, using data of Korea National Health and Nutrition Examination Survey 2012. A total of 3,344 individuals (599 cases and 2,745 controls) were analyzed in the study. Dietary data was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…reported that for every increase in daily vitamin C and vitamin A consumption by 500-mg and 5 mg, respectively, the risk of ARC decreases by 18% and 6%, respectively (38). In another study, lower intake of vitamin A and vitamin C than estimated average requirements, based on dietary reference intakes for Koreans, increased the odds of ARC (1.89 and 2.06 respectively) in crude (not adjusted) model (39). Theodoropoulou and colleagues found an inverse association between intake of sh, vegetables, fruits, potatoes, carotene, vitamins C and E, unlike meat, total fat, and cholesterol, and risk of ARC (40).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…reported that for every increase in daily vitamin C and vitamin A consumption by 500-mg and 5 mg, respectively, the risk of ARC decreases by 18% and 6%, respectively (38). In another study, lower intake of vitamin A and vitamin C than estimated average requirements, based on dietary reference intakes for Koreans, increased the odds of ARC (1.89 and 2.06 respectively) in crude (not adjusted) model (39). Theodoropoulou and colleagues found an inverse association between intake of sh, vegetables, fruits, potatoes, carotene, vitamins C and E, unlike meat, total fat, and cholesterol, and risk of ARC (40).…”
Section: Discussionmentioning
confidence: 97%
“…Accumulation of free radicals in eye lens have been implicated in development of ARC through disturbing the normal function and structural integrity of the region. Plant-based foods, rich in bioactive phytochemicals and anti-oxidative vitamins, scavenge the UV exposure-induced excessive free radicals, therefore these functional foods alleviate the oxidative damage and morphological changes of eye lens (13,38,39,46). Also, high content of omega-3 nd in sh may attenuate in ammatory responses by modulating prostaglandin metabolism (47).…”
Section: Discussionmentioning
confidence: 99%
“…The results are close to the current RNIs (Recommend) of Chinese children (360 µg RAE/d for the children aged 4–6 y, and 500 µg RAE/d for the children aged 7–11 y) [ 3 ], but lower than the RDAs of U.S. children (400 µg RAE/d for the children aged 4–8 y, and 600 µg RAE/d for the children aged 9–13 y) [ 6 , 7 ]. We also compared the results with that of the other Asian countries, Japan (450 µg RE/d for the children aged 3–8 y, and 500 µg RE/d for the children aged 8–10 y) [ 35 ], and Korean (400 µg RE/d for the children aged 6–8 y, and 500 µg RE/d (girls), 550 µg RE/d (boys) for the children aged 9–11 y) [ 36 , 37 ], and found that the results were relatively close.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicate that there is a link between dietary habits and the development of cataracts. The antioxidant properties of vitamins C and E could have a protective role against the development and progression of cataracts [ 8 - 10 ]. Also, it is suggested that the carotenoids lutein and zeaxanthin, which are antioxidants, may have a protective role against cataracts [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%